Niobium-molybdenum-based porous refractory metal-based ceramic composite material and laser metal deposition preparation method thereof

The preparation of niobium-molybdenum-based porous refractory metal-based ceramic composite materials through laser metal deposition technology has solved the problem of complex and difficult to prepare closed pore structures in the existing porous material preparation methods, and achieved low density, high strength and good forming capabilities of the material, which is suitable for lightweight design of complex structural components.

CN119614973APending Publication Date: 2025-03-14KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411932809.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing porous materials are made in complex, costly and difficult to prepare closed pore structures, which limits their application in the fields of national defense and military industry, aerospace, etc.

Method used

Laser metal deposition technology is used to prepare niobium-molybdenum porous refractory metal-based ceramic composite material, and uniform and fine closed inner holes are formed through spray granulation of alloy powder and laser melting.

Benefits of technology

It realizes the low density, high room temperature and high temperature strength of porous materials, and good processing and forming capabilities, meets the forming needs of complex structural components, and reduces the density of materials, which is suitable for lightweight designs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614973A_ABST
    Figure CN119614973A_ABST
Patent Text Reader

Abstract

The invention relates to a niobium-molybdenum-based porous refractory metal-based ceramic composite material and a laser metal deposition preparation method thereof, and belongs to the technical field of porous material science. The niobium-molybdenum-based porous refractory metal-based ceramic composite material is prepared from the following components in percentage by volume: 61.6%-78.6% of an NbMo alloy phase, 2.3%-19.3% of a carbide ceramic phase and the balance of a pore proportion, and the volume of the NbMo alloy phase, the carbide ceramic phase and the pore proportion is 100%. The porous refractory metal-based ceramic composite material prepared by the preparation method disclosed by the invention still has the compressive yield strength of 230.1 MPa at 1450 DEG C; the compression fracture strain at the room temperature reaches 32% and is 15.3 times that of the NbMoTaW refractory high-entropy alloy; the porosity can reach 32.74%; the true density is 6.17 g / cm < 3 >, and the density is only 72% of that of pure niobium and 60% of that of pure molybdenum. According to the method, the refractory alloy component with high mechanical property and low density can be obtained at low cost, and the method has potential application prospects in the fields of national defense and military industry, aerospace, electronic information, nuclear industry and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a niobium-molybdenum-based porous refractory metal-based ceramic composite material and a preparation method thereof by laser metal deposition, belonging to the technical field of porous material science. Background Art

[0002] In recent years, porous materials have attracted extensive attention from domestic and foreign scholars due to their unique properties and strong applicability. Porous materials are a kind of network-like functional materials with many interconnected or closed pores. Compared with continuous and dense materials, porous materials have the advantages of low density, large specific surface area, high specific strength, light weight, sound insulation, heat insulation, high energy absorption rate, etc., and are widely used in aerospace, electronic information, environmental protection, biomedicine and other fields.

[0003] At present, porous materials mainly include porous metal materials and porous ceramic materials. Porous metal materials have high strength and good processing and forming properties, but poor wear resistance, high temperature oxidation resistance and corrosion resistance. Although porous ceramic materials have excellent strength, high temperature oxidation resistance and wear resistance, their high brittleness, low elasticity and poor processing and forming properties seriously limit their practical applications. Therefore, it is urgent to develop a new porous material system with good comprehensive performance.

[0004] At present, the preparation methods of porous materials mainly include spark plasma sintering, melt foaming, self-propagating high temperature synthesis and dealloying, but most of them are complex and costly and can only prepare porous material components of simple shapes, which limits their actual production and application areas. Therefore, developing a new method for preparing porous materials is of great significance to broaden their application areas, simplify the process and reduce production costs.

[0005] Laser metal deposition (LMD) is an additive manufacturing technology that has gradually emerged in recent years. It can melt the coaxially transported metal powder in a specified area by computer-controlled high-energy laser beams, scan layer by layer according to the planned path, and finally realize the three-dimensional forming of metal parts. Laser metal deposition technology has the advantages of simple process, low cost, high material utilization rate, and the ability to directly form complex three-dimensional parts with high degrees of freedom. It has been widely recognized and applied in the forming of complex structural parts in the fields of national defense, aerospace, electronic information, nuclear industry, etc. At the same time, due to its small spot, shallow melting depth, and rapid melting, cooling, and solidification, the metal parts prepared by it have the advantages of fine grains, no macro-segregation, high density, high precision, and excellent mechanical properties. Laser metal deposition technology can be used to prepare components with complex spatial structures, but this technology cannot yet achieve the preparation of closed internal pore porous structures.

[0006] The present invention is devoted to developing a method for preparing a novel porous refractory metal-based ceramic composite material by utilizing laser metal deposition technology. Summary of the invention

[0007] In view of the problems and shortcomings of the above-mentioned prior art, the present invention provides a niobium-molybdenum-based porous refractory metal-based ceramic composite material and a preparation method thereof by laser metal deposition. The porous refractory metal-based ceramic composite material involved in the present invention has high room temperature and high temperature strength, uniform and fine closed inner pores, low density and good processing and forming ability, which can meet the forming requirements of complex structural components in the fields of national defense, military industry, aerospace, electronic information, nuclear industry, etc., and can further realize the lightweight design of high temperature components.

[0008] A niobium-molybdenum-based porous refractory metal-based ceramic composite material is composed of the following components in volume fraction: 61.6% to 78.6% of a NbMo alloy phase, 2.3% to 19.3% of a carbide ceramic phase, and the remainder being pores, with the volume of the three accounting for 100%.

[0009] The niobium-molybdenum-based porous refractory metal-based ceramic composite material is prepared from alloy powder by laser metal deposition or laser selective melting.

[0010] The method for preparing the alloy powder comprises the following steps:

[0011] (1) Raw material preparation: crush the Hf-Nb-Mo-Ta-C alloy into powder, then mix it evenly with polytetrafluoroethylene powder and dry it to obtain a mixed powder;

[0012] (2) Preparation of adhesive: polyvinyl alcohol and polyethylene glycol are mixed evenly to prepare an adhesive;

[0013] (3) Slurry preparation: the mixed powder obtained in step (1) and the adhesive obtained in step (2) are mixed evenly, and then anhydrous ethanol is added and stirred thoroughly to obtain a powder slurry with uniform composition;

[0014] (4) Slurry spray granulation: The powder slurry obtained in step (3) is spray granulated using a high-speed centrifugal spray dryer, with an air inlet temperature of 210 to 270° C., an air outlet temperature of 105 to 125° C., a centrifugal speed of 15 to 35 Hz, a spray blade diameter of φ0.8 to 1.2 mm, and a feed rate of 400 to 700 ml / min to prepare a spray granulated powder;

[0015] (5) Sieving and drying: The spray granulated powder obtained in step (4) is sieved through a sieve with a pore size of 45 to 105 μm, and the sieved powder is dried at 90 to 100° C. for 120 to 160 min to finally obtain a nearly spherical alloy powder.

[0016] In the step (1), the molar ratio of Hf, Nb, Mo, Ta and C in the Hf-Nb-Mo-Ta-C alloy is (0.05-0.15):(1.0-3.0):(0.2-1.2):(0.02-0.15):(0.04-0.15), and the mass of the polytetrafluoroethylene powder is 0.1%-0.3% of the mass of the Hf-Nb-Mo-Ta-C alloy.

[0017] The Hf-Nb-Mo-Ta-C alloy powder obtained in step (1) is crushed by hydrogenation and has a particle size of ≤10 μm; the particle size of the polytetrafluoroethylene powder is 1 to 3 μm.

[0018] In the step (2), polyvinyl alcohol accounts for 40-80% of the mass of the adhesive, and the remainder is polyethylene glycol.

[0019] In the step (3), the adhesive accounts for 2% to 3% of the mass of the mixed powder, and the anhydrous ethanol accounts for 20% to 30% of the total mass of the mixed powder and the adhesive.

[0020] The laser metal deposition control is as follows: laser power 5500-6500W, scanning speed 8-15mm / s, spot diameter 1-2mm, scanning spacing 1.5-2.5mm, and interlayer thickness 0.5-1mm.

[0021] The laser selective melting is controlled as follows: the laser selective melting parameters are power 800-1200W, scanning speed 30-650mm / s, spot diameter 300-500μm, and interlayer thickness 300-500μm.

[0022] The beneficial effects of the present invention are:

[0023] (1) High density is one of the main difficulties in the application of refractory alloy components. If the weight of refractory alloys can be reduced, it will have important practical application significance. Although additive manufacturing technology can manufacture complex structures and achieve lightweighting to a certain extent, this method can only manufacture components with open complex structures, and cannot manufacture components with closed inner holes (closed inner holes will block the powder inside). The technical method of the present invention can be used to manufacture components with closed inner holes, further reducing the density of refractory alloy components and meeting lightweight design requirements.

[0024] (2) The porous refractory metal-based ceramic composite material prepared by the present invention has a low density. The actual density of the porous refractory metal-based ceramic composite material prepared by the present invention is only 6.17 g / cm 3 The density is 67.26% and the porosity is as high as 32.74%. The density of the porous refractory metal-based ceramic composite material of the present invention is only 72% of that of pure niobium and 60% of that of pure molybdenum.

[0025] (3) The porous refractory metal-based ceramic composite material prepared by the present invention has good high-temperature strength and can meet the high-temperature use requirements of components. The niobium-molybdenum-based porous refractory metal-based ceramic composite material prepared by the present invention still has a compressive yield strength of 230.1MPa at 1450°C, and has good resistance to high-temperature softening, which can meet the high-temperature use requirements of components.

[0026] (4) Compared with other refractory alloys, the porous refractory metal-based ceramic composite material prepared by the present invention has outstanding plasticity, and its carbide phase is coherent with the matrix. While the carbide strengthens the matrix, it does not cause plasticity degradation. The niobium-molybdenum-based porous refractory metal-based ceramic composite material prepared by the present invention has a room temperature compression fracture strain of 32%, which is 15.3 times that of the NbMoTaW refractory high entropy alloy. Good plasticity makes the porous material less likely to crack during the additive forming process and easier to process and form.

[0027] (5) The porous refractory metal-based ceramic composite material prepared by the present invention has good room temperature strength, and its carbide phase is coherent with the matrix, which significantly strengthens the material. The niobium-molybdenum-based porous refractory metal-based ceramic composite material prepared by the present invention has a compressive yield strength of 472.9 MPa at room temperature.

[0028] (6) The addition of Hf element can regulate the type of carbide ceramic phase. Compared with other elements in the alloy, Hf element and C element have the largest negative mixing enthalpy value. Therefore, the carbide ceramic phase precipitated in the alloy is MC-type carbide with FCC structure, and is completely coherent with the matrix, ensuring good room temperature plasticity.

[0029] (7) After spray granulation, the polytetrafluoroethylene powder with smaller particle size is uniformly adsorbed on the nearly spherical alloy powder, and decomposed and vaporized under the action of the high-energy laser beam, thereby forming uniform and fine pores inside the alloy material.

[0030] (8) The preparation process of porous refractory metal-based ceramic composites is simple, easy to operate, low cost and high material utilization. Compared with several commonly used methods, the use of laser metal deposition technology greatly shortens the sample preparation cycle and can obtain porous refractory metal-based ceramic composites with uniform and fine structure, no macroscopic segregation, no impurity pollution, uniform and fine pores and excellent mechanical properties.

[0031] (9) The porous refractory metal-based ceramic composite material prepared by the present invention has low density, good plasticity, and high high-temperature strength. Its preparation process is simple and it is expected to be used in the forming of complex structural components at the hot end in the fields of national defense, military industry, aerospace, electronic information, nuclear industry, etc., and meet the requirements of lightweight design. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1This is a macroscopic morphology of a porous refractory metal-based ceramic composite material sample prepared in Example 1 of the present invention;

[0033] Figure 2 The porous refractory metal-based ceramic composite material compression sample prepared in Example 1 of the present invention;

[0034] Figure 3 This is a 500-fold metallographic image of the porous refractory metal-based ceramic composite material prepared in Example 1 of the present invention;

[0035] Figure 4 This is a room temperature compressive stress-strain curve of the porous refractory metal-based ceramic composite material prepared in Example 1 of the present invention;

[0036] Figure 5 This is a 1450°C compressive stress-strain curve of the porous refractory metal-based ceramic composite material prepared in Example 1 of the present invention;

[0037] Figure 6 This is a SEM image of the porous refractory metal-based ceramic composite material prepared in Example 1 of the present invention;

[0038] Figure 7 This is the XRD spectrum of the porous refractory metal-based ceramic composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0039] The present invention will be further described below in conjunction with the accompanying drawings and specific implementation methods.

[0040] Example 1

[0041] The niobium-molybdenum-based porous refractory metal-based ceramic composite material is composed of the following components in volume fraction: 73.3% of NbMo alloy phase, 7.6% of carbide ceramic phase, and the remainder is pores, and the volume of the three is 100%.

[0042] The niobium-molybdenum-based porous refractory metal-based ceramic composite material is prepared from alloy powder by laser metal deposition or laser selective melting, and comprises the following steps:

[0043] (1) Raw material preparation: crush the Hf-Nb-Mo-Ta-C alloy into powder (the molar ratio of Hf, Nb, Mo, Ta and C in the Hf-Nb-Mo-Ta-C alloy is 0.1:1.6:0.3:0.04:0.14, and the alloy powder is obtained by hydrogenation crushing, with a particle size of ≤10 μm), and then mix it with polytetrafluoroethylene powder (the mass of the polytetrafluoroethylene powder is 0.15% of the mass of the Hf-Nb-Mo-Ta-C alloy, and the particle size is <1 μm) and dry it at 90° C. for 120 min to obtain a mixed powder;

[0044] (2) Preparation of adhesive: Polyvinyl alcohol (60% by weight of the adhesive) and polyethylene glycol (40% by weight of the adhesive) were uniformly mixed to prepare an adhesive;

[0045] (3) Preparation of slurry: The mixed powder obtained in step (1) and the adhesive (2.5% of the total mass of the mixed powder) obtained in step (2) are mixed evenly, and then anhydrous ethanol (25% of the total mass of the mixed powder and the adhesive) is added and stirred thoroughly to obtain a powder slurry with uniform composition;

[0046] (4) Slurry spray granulation: The powder slurry obtained in step (3) was spray granulated using a high-speed centrifugal spray dryer with an air inlet temperature of 240° C., an air outlet temperature of 115° C., a centrifugal speed of 25 Hz, a spray blade diameter of φ1.0 mm, and a feed rate of 550 ml / min to prepare a spray granulated powder;

[0047] (5) Sieving and drying: The spray granulated powder obtained in step (4) is sieved through a sieve with a pore size of 45 to 105 μm, and the sieved powder is dried at 95° C. for 150 min to finally obtain a nearly spherical alloy powder.

[0048] (6) Laser metal deposition control: Nearly spherical alloy powder was prepared by laser metal deposition to obtain a niobium-molybdenum-based porous refractory metal-based ceramic composite material with a laser power of 6000 W, a scanning speed of 10 mm / s, a spot diameter of 1.2 mm, a scanning interval of 1.5 mm, and an interlayer thickness of 0.6 mm.

[0049] The macroscopic morphology of the porous refractory metal-based ceramic composite material sample prepared in this embodiment is shown in FIG. Figure 1 As shown, from Figure 1 It can be seen that the composite material is well formed, with no cracks on the surface and no open pores.

[0050] Figure 2 The porous refractory metal-based ceramic composite material prepared in this embodiment is used to prepare a compression sample by wire cutting. The internal cross-sectional morphology is as follows: Figure 2 As shown, from Figure 2 It can be seen that a large number of holes can be seen on the surface of the sample, which indicates that the composite material prepared in this embodiment has a large number of uniform and small closed internal pores.

[0051] The 500-fold metallographic image of the porous refractory metal-based ceramic composite material prepared in this embodiment is as follows: Figure 3 As shown, from Figure 3 It can be seen that the composite material has uniform composition, no segregation, and fine grains.

[0052] The room temperature compressive stress-strain curve of the porous refractory metal-based ceramic composite material prepared in this embodiment is shown in FIG. Figure 4As shown, from Figure 4 It can be seen that the compressive yield strength of the composite material at room temperature is 472.9 MPa, and the compressive fracture strain is 32%, which is 15.3 times that of the NbMoTaW refractory high entropy alloy, and has good room temperature plasticity.

[0053] The 1450°C compressive stress-strain curve of the porous refractory metal-based ceramic composite material prepared in this embodiment is shown in FIG. Figure 5 As shown, from Figure 5 It can be seen that the compressive yield strength of the composite material at 1450°C is 230.1 MPa, which has high high temperature strength.

[0054] The SEM image of the porous refractory metal-based ceramic composite material prepared in this embodiment is as follows Figure 6 As shown, from Figure 6 It can be seen that the alloy grains are relatively small, and many carbide ceramic phases are precipitated at the grain boundaries.

[0055] The XRD spectrum of the porous refractory metal-based ceramic composite material prepared in this example is as follows Figure 7 As shown, it is proved that the chemical formula of the porous refractory metal-based ceramic composite material prepared by the present invention is Hf 0.1 Nb 1.6 Mo 0.3 Ta 0.04 C 0.14 .

[0056] The porous refractory metal-based ceramic composite material prepared by the present invention has a true density of only 6.17 g / cm 3 The density is 67.26% and the porosity is as high as 32.74%. The density of the porous refractory metal-based ceramic composite material of the present invention is only 72% of that of pure niobium and 60% of that of pure molybdenum.

[0057] Example 2

[0058] The niobium-molybdenum-based porous refractory metal-based ceramic composite material is composed of the following components in volume fraction: 75.4% of NbMo alloy phase, 5.5% of carbide ceramic phase, and the remainder is pores, and the volume of the three is 100%.

[0059] The niobium-molybdenum-based porous refractory metal-based ceramic composite material is prepared from alloy powder by laser metal deposition or laser selective melting, and comprises the following steps:

[0060] (1) Raw material preparation: crush the Hf-Nb-Mo-Ta-C alloy into powder (the molar ratio of Hf, Nb, Mo, Ta and C in the Hf-Nb-Mo-Ta-C alloy is 0.08:1.5:0.5:0.02:0.1, and the alloy powder is obtained by hydrogenation crushing, with a particle size of ≤10 μm), then mix it with polytetrafluoroethylene powder (the mass of the polytetrafluoroethylene powder is 0.25% of the mass of the Hf-Nb-Mo-Ta-C alloy, and the particle size is <1 μm), and dry it at 85° C. for 100 min to obtain a mixed powder;

[0061] (2) Preparation of adhesive: Polyvinyl alcohol (50% by weight of the adhesive) and polyethylene glycol (50% by weight of the adhesive) were uniformly mixed to prepare an adhesive;

[0062] (3) Preparation of slurry: The mixed powder obtained in step (1) and the adhesive (2.1% of the total mass of the mixed powder) obtained in step (2) were mixed evenly, and then anhydrous ethanol (23% of the total mass of the mixed powder and the adhesive) was added and stirred thoroughly to obtain a powder slurry with uniform composition;

[0063] (4) Slurry spray granulation: The powder slurry obtained in step (3) was spray granulated using a high-speed centrifugal spray dryer, with an inlet air temperature of 220° C., an outlet air temperature of 110° C., a centrifugal speed of 20 Hz, a spray piece diameter of φ0.8 mm, and a feed rate of 500 ml / min to prepare a spray granulated powder;

[0064] (5) Sieving and drying: The spray granulated powder obtained in step (4) is sieved through a sieve with a pore size of 15 to 53 μm, and the sieved powder is dried at 90° C. for 120 min to finally obtain a nearly spherical alloy powder.

[0065] (6) Laser selective melting control: Nearly spherical alloy powders were prepared by laser selective melting to obtain niobium-molybdenum-based porous refractory metal-based ceramic composites. The laser selective melting parameters were power 1000 W, scanning speed 30 mm / s, spot diameter 500 μm, and interlayer thickness 400 μm.

[0066] Example 3

[0067] The niobium-molybdenum-based porous refractory metal-based ceramic composite material is composed of the following components in volume fraction: 71.9% of NbMo alloy phase, 9.1% of carbide ceramic phase, and the remainder is pores, and the volume of the three is 100%.

[0068] The niobium-molybdenum-based porous refractory metal-based ceramic composite material is prepared from alloy powder by laser metal deposition or laser selective melting, and comprises the following steps:

[0069] (1) Raw material preparation: crushing the Hf-Nb-Mo-Ta-C alloy into powder (the molar ratio of Hf, Nb, Mo, Ta and C in the Hf-Nb-Mo-Ta-C alloy is 0.05:1.8:0.2:0.07:0.12, the alloy powder is obtained by hydrogenation crushing, and the particle size is ≤10 μm), then mixing with polytetrafluoroethylene powder (the mass of the polytetrafluoroethylene powder is 0.1% of the mass of the Hf-Nb-Mo-Ta-C alloy, and the particle size is <1 μm) and drying at 85° C. for 100 min to obtain a mixed powder;

[0070] (2) Preparation of adhesive: Polyvinyl alcohol (55% by weight of the adhesive) and polyethylene glycol (45% by weight of the adhesive) were uniformly mixed to prepare an adhesive;

[0071] (3) Preparation of slurry: The mixed powder obtained in step (1) and the adhesive (2.8% of the total mass of the mixed powder) obtained in step (2) are mixed evenly, and then anhydrous ethanol (28% of the total mass of the mixed powder and the adhesive) is added and stirred thoroughly to obtain a powder slurry with uniform composition;

[0072] (4) Slurry spray granulation: The powder slurry obtained in step (3) was spray granulated using a high-speed centrifugal spray dryer with an air inlet temperature of 260°C, an air outlet temperature of 120°C, a centrifugal speed of 30 Hz, a spray blade diameter of φ1.2 mm, and a feed rate of 650 ml / min to prepare a spray granulated powder;

[0073] (5) Sieving and drying: The spray granulated powder obtained in step (4) is sieved through a sieve with a pore size of 15 to 53 μm, and the sieved powder is dried at 90° C. for 120 min to finally obtain a nearly spherical alloy powder.

[0074] (6) Laser selective melting control: Nearly spherical alloy powder was prepared by laser selective melting to obtain niobium-molybdenum-based porous refractory metal-based ceramic composite materials. The laser selective melting parameters were as follows: power 1200 W, scanning speed 650 mm / s, spot diameter 300 μm, and interlayer thickness 300 μm.

[0075] The specific implementation modes of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

Claims

1. A niobium-molybdenum-based porous refractory metal-based ceramic composite material, characterized in that: It is composed of the following components in volume fractions: 61.6% to 78.6% of NbMo alloy phase, 2.3% to 19.3% of carbide ceramic phase, and the remainder is pores, and the volume of the three is 100%.

2. A method for preparing the niobium-molybdenum-based porous refractory metal-based ceramic composite material according to claim 1, characterized in that: The niobium-molybdenum-based porous refractory metal-based ceramic composite material is prepared from alloy powder by laser metal deposition or laser selective melting.

3. The method for preparing the niobium-molybdenum-based porous refractory metal-based ceramic composite material according to claim 2, characterized in that: The method for preparing the alloy powder comprises the following steps: (1) Raw material preparation: crush the Hf-Nb-Mo-Ta-C alloy into powder, then mix it evenly with polytetrafluoroethylene powder and dry it to obtain a mixed powder; (2) Preparation of adhesive: polyvinyl alcohol and polyethylene glycol are mixed evenly to prepare an adhesive; (3) Slurry preparation: the mixed powder obtained in step (1) and the adhesive obtained in step (2) are mixed evenly, and then anhydrous ethanol is added and stirred thoroughly to obtain a powder slurry with uniform composition; (4) Slurry spray granulation: The powder slurry obtained in step (3) is spray granulated using a high-speed centrifugal spray dryer, with an air inlet temperature of 210 to 270° C., an air outlet temperature of 105 to 125° C., a centrifugal speed of 15 to 35 Hz, a spray blade diameter of φ0.8 to 1.2 mm, and a feed rate of 400 to 700 ml / min to prepare a spray granulated powder; (5) Sieving and drying: The spray granulated powder obtained in step (4) is sieved through a sieve with a pore size of 45 to 105 μm, and the sieved powder is dried at 90 to 100° C. for 120 to 160 min to finally obtain a nearly spherical alloy powder.

4. The method for preparing the niobium-molybdenum-based porous refractory metal-based ceramic composite material according to claim 3, characterized in that: In the step (1), the molar ratio of Hf, Nb, Mo, Ta and C in the Hf-Nb-Mo-Ta-C alloy is (0.05-0.15):(1.0-3.0):(0.2-1.2):(0.02-0.15):(0.04-0.15), and the mass of the polytetrafluoroethylene powder is 0.1%-0.3% of the mass of the Hf-Nb-Mo-Ta-C alloy.

5. The method for preparing the niobium-molybdenum-based porous refractory metal-based ceramic composite material according to claim 3, characterized in that: The Hf-Nb-Mo-Ta-C alloy powder obtained in step (1) is crushed by hydrogenation, and has a particle size of ≤10 μm; the particle size of the polytetrafluoroethylene powder is 1 to 3 μm.

6. The method for preparing the niobium-molybdenum-based porous refractory metal-based ceramic composite material according to claim 3, characterized in that: In the step (2), polyvinyl alcohol accounts for 40-80% of the mass of the adhesive, and the remainder is polyethylene glycol.

7. The method for preparing the niobium-molybdenum-based porous refractory metal-based ceramic composite material according to claim 3, characterized in that: In the step (3), the adhesive accounts for 2% to 3% of the mass of the mixed powder, and the anhydrous ethanol accounts for 20% to 30% of the total mass of the mixed powder and the adhesive.

8. The method for preparing the niobium-molybdenum-based porous refractory metal-based ceramic composite material according to claim 2, characterized in that: The laser metal deposition is controlled to have a laser power of 5500-6500 W, a scanning speed of 8-15 mm / s, a spot diameter of 1-2 mm, a scanning interval of 1.5-2.5 mm, and an interlayer thickness of 0.5-1 mm.

9. The method for preparing the niobium-molybdenum-based porous refractory metal-based ceramic composite material according to claim 2, characterized in that: The laser selective melting is controlled as follows: the laser selective melting parameters are power 800-1200W, scanning speed 30-650mm / s, spot diameter 300-500μm, and interlayer thickness 300-500μm.